Short Communication: Microfungal diversity on leaves of Eusideroxylon zwageri, a threatened plant species in Sarawak, Northern Borneo - A LATEEF ADEBOLA; MUID SEPIAH; MOHAMAD H BOLHASSAN; MANSOR WAN ZAMIR (Biodiversitas Journal of Biological Diversity, 2015)
Adebola AL, Sepiah M, Bolhassan MH, Wan Zamir M. 2015. Microfungal diversity on leaves of Eusideroxylon zwageri, athreatened plant species in Sarawak, Northern Borneo. Biodiversitas 16: 264-268. A survey of the microfungal communities on greenleaves and leaf litters of an endangered plant species, Eusideroxylon zwageri Teijsm. & Binn. (belian) was carried out for the first time.A total of 200 leaf segments were plated on both water agar and malt extract agar. 74 fungal species were identified from both leaf typeswith more fungal taxa found on the green leaves, with a Shannon diversity index of 3.85 compared to that on litters, 2.63 and thesimilarity between the microfungal communities on both leaf types was low with a Bray-Curtis similarity index of 0.366. The mostdominant species on both leaf types includes Aphanocladium areanarum, Trichoderma koningii, Nectria sp., Chalara pteridina,Hyphomycetes sp.3, hyaline Mycelia sterilia, Circinotrichum sp., Phoma sp., Acremonium macroclavatum, Chaetopsina sp., Physarumsp., Beltrania rhombica and Colletotrichum acutatum.